Fetal abdominal cysts: Predicting adverse outcomes - Paula Garcia‐Aguilar; Nerea Maiz; Carlota Rodó; Pablo Garcia‐Manau; Silvia Arévalo; Jose Andres Molino; Gabriela Guillen; Elena Carreras (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction The primary aim of the study was to identify risk factors associated with fetal or neonatal loss, neonatal morbidity, and the need for surgery in fetuses diagnosed with an abdominal cyst. The secondary aim was to compare the characteristics of the cyst according to trimester at diagnosis. Material and methods This was an observational retrospective study performed at Vall d'Hebron University Hospital. The study included pregnant women aged 18 years or older with diagnosis of a fetal abdominal cyst from 2008 to 2021. Results A total of 82 women with a median gestational age of 31+1 weeks (12+0–39+4) were included in the analysis. Seven (8.5%) cases were diagnosed in the first trimester, 28 (34.1%) in the second trimester, and 47 (57.3%) in the third trimester. Fetal or neonatal loss occurred in 10 (12.2%) cases; significant predictors were diagnosis in the first trimester (OR 36.67, 95% CI: 4.89–274.79), male gender (OR 4.75, 95% CI: 1.13–19.9), and associated abnormalities (OR 15.2, 95% CI: 2.92–79.19). A total of 10 of 75 (13.3%) neonates showed at least one neonatal complication, and the only predictor was occurrence of associated abnormalities (OR 7.36, 95% CI: 1.78–30.51). A total of 16 of 75 (21.3%) neonates required postnatal surgery, and the predictors were second‐trimester diagnosis (OR 3.92, 95% CI: 1.23–12.51), associated abnormalities (OR 3.81, 95% CI: 1.15–12.64), and bowel location (OR 10.0, 95% CI: 1.48–67.55). Conclusions Factors associated with adverse outcomes in fetuses diagnosed with abdominal cysts are first‐trimester diagnosis and associated abnormalities. Cysts detected in the second trimester and those of intestinal origin are more likely to require surgery.